Modelo para la exposición de la materia de ingeniería de software. - Rayas, L.; Abreu, J. L. (Revista Daena: International Journal of Good Conscience, 2008)
With this Project was designed a teaching model that counts on a useful tool to guide the teacher to facilitate the engineering software I class, in a structured way and taking into consideration the actual methodologies for the process of documentation of the development of software, from its most elemental foundations, as the adequate recompilation of requirements, such as functionalism and the administration of projects identifying the critical route and to determine the delivery times, calendarization of the total project and its monitoring.